The Longitudinal Evolution of Cerebral Blood Flow Regulation after Acute Ischaemic Stroke - Salinet, Angela S.M. (S. Karger AG, 2014)
BACKGROUND: Acute stroke is known to impair cerebral blood flow (CBF) regulation, but the longitudinal changes of these effects have been poorly reported. The main CBF regulatory mechanisms [cerebral autoregulation (CA) and neurovascular coupling (NVC)] were assessed over 3 months after acute ischaemic stroke. METHODS: Recordings of CBF velocity (CBFv), blood pressure (BP), and end-tidal CO(2) were performed during 5 min baseline and 1 min passive movement of the elbow. Stroke patients were assessed <72 h of stroke onset, and at 2 weeks, 1 and 3 months after stroke. RESULTS: Fifteen acute stroke subjects underwent all 4 sessions and were compared to 22 control subjects. Baseline recordings revealed a significantly lower CBFv in the affected hemisphere within 72 h after stroke compared to controls (p = 0.02) and a reduction in CA index most marked at 2 weeks (p = 0.009). CBFv rise in response to passive arm movement was decreased bilaterally after stroke, particularly in the affected hemisphere (p < 0.01). Both alterations in CA and NVC returned to control levels during recovery. CONCLUSION: The major novel finding of this study was that both CA and NVC regulatory mechanisms deteriorated initially following stroke onset, but returned to control levels during the recovery period. These findings are relevant to guide the timing of interventions to manipulate BP and potentially for the impact of intensive rehabilitation strategies that may precipitate acute physiological perturbations but require further exploration in a larger population that better reflects the heterogeneity of stroke. Further, they will also enable the potential influence of stroke subtype to be investigated.